Formulation and characterization of surfactants with antibacterial and corrosion-inhibiting properties for enhancing shale gas drainage and production - Jia Li; Ming Wen; Zeyin Jiang; Shangjun Gao; Xiao Xiao; Chao Xiang; Ji Tao (Scientific Reports)
Abstract A Gemini cationic surfactant was synthesized through an aldehyde-amine condensation reaction to address challenges related to bacterial corrosion and foaming during shale gas extraction. This treatment agent exhibits sterilization, corrosion mitigation, and foaming properties. The mechanism of action was characterized through tests measuring surface tension, particle size, sterilization efficacy, corrosion mitigation efficiency, and foaming behavior. Results from the surface tension test indicate that at 60 °C, surfactants with a low carbon chain structure achieve the lowest surface tension of 32.61 mN/m at the critical micelle concentration. Particle size distribution (PSD) tests reveal that within the 1–10 critical micelle concentration range, three types of surfactants can form aggregates through self-assembly, with a PSD range of 100–400 nm. Antibacterial performance tests demonstrate that a concentration of 0.12 mmol/L at 20–60 °C achieves a bactericidal rate exceeding 99%, maintained even after 24 h of contact. The bactericidal effect is enhanced under acidic and alkaline conditions. Corrosion mitigation tests show that at 50 °C, the corrosion mitigation rate reaches an optimal value of over 70%. Bubble performance evaluation results suggest that the optimal surfactant concentration is 1 mmol/L at 60 °C, exhibiting resistance to mineralization up to 200 g/L. The development of this surfactant establishes a foundation for effectively addressing issues related to bacterial corrosion and wellbore fluid encountered in shale gas wells.